Efek Polutan Logam Berat Pada Sungai di Indonesia Terhadap Biota Aquatik - Amirunnas, Amirunnas; Chairunnisa, Nikitha; Firdus, Firdus; Rizki, Alia; Nasir, Muhammad (Universitas Batangahari Jambi, 2025)
Heavy metals are pollutants that cause detrimental poisoning in various aquatic biota. This article compiles the results of various studies into a review of their sources, distribution, rejection and impact on aquatic biota. Over time, the compilation of organic and inorganic arsenic, Pb, Cd, and Hg detected significantly increased in shellfish in most of the rivers included in this article. From the results, the affected areas and their river biota, a small number of eye health surveys conducted, including possible cures, are presented by discussing the utility of remediation and preventative measures through regulatory changes.